A Dendralenic C–H Acid - Höfler, Denis; Goddard, Richard; Nöthling, Nils; List, Benjamin (Synlett, 2019)
The design and synthesis of a strong, dendralenic C–H acid is described. Crystal structure analyses confirm the proposed structure. Despite the moderate stability of our motif, an application to Brønsted acid catalysis has been explored.
Keywords: dendralenic C–H acids; cross-conjugated acids; triflyl groups; strong acids; non-coordinating anions; Brønsted acids